Nutrient intakes of pregnant and lactating women in Indonesia and Malaysia: Systematic review and meta-analysis - Agustina, Rina; Rianda, Davrina; Lasepa, Wanda; Birahmatika, Fitya S.; Stajic, Vladimir; Mufida, Rachmi (Frontiers in Nutrition, 2023)
Introduction Optimizing dietary intake during pregnancy and lactation is crucial to the growth and development of children and their lifelong health. We performed a systematic review and meta-analysis to describe the nutrient intakes of pregnant and lactating women in Indonesia and Malaysia, countries that are experiencing rapid nutrition transition in Southeast Asia. Methods We screened 2,258 studies published between January 1980 and March 2021. The nutrient intakes of pregnant and lactating women were quantitatively analyzed to calculate the percentage of adequacy using national recommended daily allowances or nutrient intakes (RDA/RNI) and estimated average requirements (EAR) for micronutrients. Standardized mean differences (SMD) between dietary intake and RDA/RNI were determined for selected nutrients. Results Fifty-three studies were included and showed that energy and macronutrient intakes among pregnant and lactating women in both countries were below the RDA/RNI. In addition, most studies reported that women failed to meet the EAR for vitamin D (<70% EAR), vitamin E (<50% EAR), and water-soluble vitamins (<80% EAR) except for vitamin C and A among Malaysians. Moreover, calcium, potassium, and iron intakes of pregnant women were <60% EAR in Indonesia and <80% EAR in Malaysia. Phosphorus intake among pregnant women in both countries and sodium intake among Malaysian pregnant women exceeded 100% EAR. Indonesian lactating women had <60% EAR for calcium and potassium intakes, while Malaysian women had more than 100% EAR. For 21 studies reporting overall protein intakes, the standard mean difference (SMD) was −2.26 (95% CI; −2.98, −1.54) below the RDA/RNI for pregnant women and −0.67 SMD (95% CI −15.7, −11.5) for lactating women. When the four studies from Malaysia were analyzed separately, protein intakes of pregnant women were above the RNI. Moreover, low intakes of vitamin D, vitamin C, calcium, and iron, but sufficient intakes in vitamin A, zinc, and phosphorus were observed in pregnant women in both countries. Conclusion Dietary intakes of energy, macronutrients, and micronutrients (vitamin D, vitamin E, water-soluble vitamins, calcium, and iron) of pregnant and lactating women in Indonesia and Malaysia were below the recommendations. Important heterogeneities were observed even between these two countries for specific essential nutrient intakes. Innovative research and targeted programs to address specific deficiencies should be prioritized. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021252204, identifier: CRD42021252204.